Uang-Uang Yang Dapat Ditatausakan oleh Balai Harta Peninggalan - Evi Anastasia (UNES Law Review, 2023)
Probate Office is a technical implementation unit under Directorate General of Legal Administrative Affairs of Ministry of Law and Human Rights, have some authority, among them is to administer money, obtained from sales or rent from asset belongs to person who is absence, unattended asset, other asset because of law, and other asset because court ruling or order. Ministerial Decree of Law and Human Rights Number 20 Year 2019 Regarding Administration of Third Party Money does not arrange about further definition about asset belongs to person who is absence and unattended asset but in Civil Code there was explanation regarding that. Meanwhile, assets because of law are assets that can be administrated by Probate Office because they are regulated by Indonesia Act. Furthermore, other asset because court ruling or order, can be administrated by Probate Office, because it legally binding, as evidence and executable. The research method used is normative judicial legal method are the method of collecting and referring to legal literature in order to study and analyse the problem.